Physical symptoms and psychological health status by the type of job. - Kawada T; Suzuki S (Work, 2008)
Background: The physical symptoms and mental health status of 3,447 men working in a dairy product company were evaluated by a health questionnaire, the Todai Health Index (THI). The purpose of this study is to determine the relationship between job content and subjective health status. Method: The authors conducted a cross-sectional study. Thirty-three branches of the company are distributed throughout Japan. The subjects ranged in age from 18 to 59 years old. The THI is composed of 130 questions and each subject's physical and mental health status was evaluated based on the scores in 13 specific scales. The subjects' jobs were classified into three categories: 1 production process work; 2 clerical or technical work; 3 transportation or sales work. Subjects grouped into the clerical or technical work category were set as the control group, because the authors speculated that the lowest workload was observed in group of clerical or technical work. Results: The scores in each of the THI scales were compared among workers in the three job categories stratified by the age group (10-year age groups). The transportation or sales workers began to show high scores for irregularity of lifestyle from their 30's, and this was maintained until subjects' retirement from the company. In addition, the same group also began to show higher scores for physical symptoms, such as vague complaints, respiratory complaints, and eye complaints from their 40's and higher scores for mouth and evacuation and digestive complaints from their 50's. Conclusions: Transportation or sales workers should receive adequate health care to prevent a high prevalence of physical and/or illness.